PENGARUH GOOGLE EARTH PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA SMA NEGERI 10 PONTIANAK - Iza Saputri,; Sri Buwono; Ludovicus Maditya Hari Christanto (Universitas Tanjungpura, 2020)
Abstract This research aims to determine whether there are differences in average learning outcomes in classes using Google Earth media with classes that use Power Point media at Senior High School 10 Pontianak. Participants in this study were class XI IPS 3 and class XI IPS 2. The method in this research was the experimental method. The form of research was quasi experimental design, namely nonequevalent control group design. Based on research calculations, there is an increase in average learning outcomes in classes using Google Earth media and classes using Power Point media. The average learning outcomes of classes using Google Earth media amounted to 85.63 and on classes using Power Point media amounted to 80.00. Based on the calculation of separated variance formula, it is known that tcount is 2.57 while ttable is 1.65, it was concluded that there are differences in learning outcomes in classes using Google Earth media and classes using Power Point media in class XI of Senior High School 10 Pontianak. Based on the Effect Size calculation, the value of 0.65 means that Google Earth media has a moderate effect on learning outcomes in class XI of Senior High School 10 Pontianak. Keywords: Influence, Goole Earth Media, Learning Outcomes.